An Ehrling-type inequality for the closed injective hull of Bloch ideals - A. Jiménez-Vargas; María Isabel Ramírez (Journal of Inequalities and Applications)
Abstract The concept of injective hull of ideals of normalized Bloch mappings is introduced and a characterization is established in terms of a domination property. The injective hulls of normalized Bloch ideals generated by the procedures of composition and duality are described and applied to concrete examples of normalized Bloch ideals. A Bloch variant of a known characterization due to Jarchow and Pelczyński for the closed injective hull of an operator ideal is stated in terms of an Ehrling-type inequality.